Lean/Sizzurp Ingredients, Use, and Coping With Mental Health Symptoms - Orrin D Ware (SAGE Publishing, 2023)
The substance combination of codeine and promethazine, commonly termed lean / sizzurp , has been identified as a method that some individuals use to cope with PTSD and other mental health symptomology. A sample of 1423 adults with self-reported past year lean use was recruited from substance-related Reddit pages to complete a survey about lean, including information about using lean to cope with emotions, thoughts, or feelings. To be included in the sample, persons needed to: (1) be ⩾18 years old, (2) report past year lean use, (3) complete lean use screeners, and (4) pass data quality checks (eg, bot detection). As Reddit is an online forum, no geographic restrictions were placed on study participation. Data on demographic characteristics, lean use, and mental health disorder symptomology were captured from participants. Logistic regression models included anxiety, depression, and trauma as independent variables along with covariates to examine using lean to cope with emotions, thoughts, or feelings in the past 30 days. Most participants were male (n = 1102; 77.4%), with an average age of 26.9 (SD = 5.2) years. Most participants used included codeine as an ingredient in lean (n = 1060; 74.5%); promethazine was added as an ingredient by 31.7% of the sample (n = 451), and the combination of codeine and promethazine was included as ingredients by 13.5% (n = 192) of the sample. Participants with anxiety, lifetime trauma exposure, and who were female had increased odds of using lean to cope with emotions, thoughts, or feelings in the past 30 days. Those with depression and unstable housing exhibited decreased odds of using lean to cope with emotions, thoughts, or feelings in the past 30 days. This study recruited persons via social media to learn more about lean use, especially lean use to cope with mental health symptoms; future population-level studies are needed.